Safety drinking water and risk of stunting in children: Is it related ? - Ratnayani Ratnayani (Indonesian Nutrition Association, 2023)
Slum areas are identic with nutritional problems in children including stunted children. Incidence of stunted can be caused by various factors, one of which is dysbiosis. This study aims to analyze the microbiota composition of stunted and non-stunted children in Jakarta slum areas and related contributing factors.